Employing a serious game intervention to promote adolescent school children's perceptions of nursing and midwifery professions - Gary Mitchell; Debbie Rainey; Maria Healy; Tara Anderson; Patrick Stark; Felicity Agwu Kalu; Catherine Monaghan; Mark A Linden (BMC, 2024)
Abstract Aim To test a serious game intervention about nursing and midwifery perceptions among adolescent school children. Background Nursing and midwifery professions face challenges in recruitment, with persistent gender stereotypes and a lack of clarity regarding the roles contributing to this issue. This study addresses the need for innovative approaches to reshape perceptions and encourage career exploration in adolescent school children. Design Employing a pre/post-test design, this study involved 137 post-primary students aged sixteen or seventeen in the United Kingdom. Methods Data collection occurred between November 2022 to April 2023, involving three post-primary schools. Participants engaged with a digital serious game designed to address misconceptions and promote a more accurate understanding of nursing and midwifery. Participants completed pre- and post-intervention questionnaires, including an adapted version of the Nursing as a Career Choice Questionnaire. Statistical analyses included descriptive statistics, paired t-tests, and independent groups t-tests. Results The serious game intervention resulted in statistically significant improvements in students' perceptions across multiple domains. Overall, participants showed higher mean post-test scores (M = 139.57, SD = 15.10) compared to their mean pre-test score (M = 131.06, SD = 14.73) on the questionnaire. The domains of self-efficacy (p < .001), job prospects (p < .001) and social influences (p < .001) exhibited the most substantial positive changes. Female participants showed higher perceptions than males in pre- and post-tests and students from all-girls schools consistently scored higher than those from all-boys and mixed-gender schools. Conclusions A serious game about the nursing and midwifery professions appears to be capable of changing perceptions of self-efficacy and job prospects related to nursing and midwifery professions. The study suggests that a serious game intervention may have the potential to change adolescent perceptions of nursing and midwifery professions which may lead to their considering of these when making future career choices.